Wikispeech - Wettin, Karl (Septentrio Conference Series, 2021)
Wikispeech is a free and open text-to-speech (TTS) solution that runs on MediaWiki. Wikispeech will make the Wikimedia projects speak – for anyone, illiterate, blind, or just belonging to the quarter of the world's population who prefer learning from listening rather than reading. In the true Wikimedia fashion, volunteers will be able to improve the quality of Wikispeech. Errors and flaws can be corrected, and in the long run, new voices and languages can be added. As part of the project, tools for collecting speech data will be developed. With this data, new voices can be created. And both the tools and the data will of course be released under a free license, so that they can be used in other speech technology projects too.